Pengaruh Financial Development Terhadap International Trade Dengan Foreign Exchange Reserves Sebagai Moderasi: Studi Negara D-8 - Fajriyatul Abadiyah; Abdul Haris (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
This study aims to analyze the influence of the financial development index on international trade in D-8 countries and examine whether foreign exchange reserves as a moderation variable are able to moderate the relationship between financial development and international trade in D-8 countries. This study included quantitative research with secondary data types sourced from the world bank and international monetary fund in the observation period from 2011 to 2020. The population in this study is a member of the Developing Eight Countries, with a sampling technique using purposive sampling. This research method uses panel data regression (ordinary least square) and moderated regression analysis (MRA) interaction test through the Eviews 10 program. The results showed that if there is a positive and significant influence between financial development and international trade, similar results are also found in foreign exchange reserves, which are used as moderation variables that significantly affect international trade. Meanwhile, the variable interaction of financial development and foreign exchange reserves has a negative influence on international trade in D-8 countries